Ecología de la avifauna de la región de Puerto Lobos, provincias de Río Negro y del Chubut - Contreras, Julio Rafael (Ecosur, 2025)
Ecologic and faunistic studies were carried out in the southwestem región of the Department of San Antonio (Province of Rio Negro) and in the northwest of the Department Biedma (Province of Chubut) during the months of January 1973 and 1974. Puerto Lobos, a small village in the Atlantic coast, at 42° S and 65° 05’ W, is the main locality in that región. The studied area is included in the Floristic Province of the Monte, and in the Zoogeographic Dominion of Patagonia, and is characterized by its aridity, with a permanent déficit of atmospheric saturation (50 to 55 o/o of mean relative humidity) and a mean annual rainfall of about 200 mm. The relief is characterized in the west side of the area by fíat plains of about 150 m high, decreasing eastward by gentle slopes or by steep slopes dissected by a disorganized and variable network of drainage gorges and dry streams, most of which are endorreic, ending in depresions or small basins of interior drainage with a salínized soil in the surface. Near the Atlantic coast the sea influence is shown by the penetration of tidal or occasionally flooded areas in the continental landscape. On the basis of the ecological distribution of the avifauna, nine difierent units were described, each one corresponding to a phisiographic characteristic type.